A Light‐Activated Microheater for the Remote Control of Enzymatic Catalysis. Issue 3 (25th November 2015) - Cao, Yuanyuan; Wang, Zhen; Liao, Shenglong; Wang, Jian; Wang, Yapei
Abstract: The remote control of enzymatic catalysis is of significant importance in disease treatment and industrial applications. Herein, we designed a microheater composed of a porous polylactic acid (PLA) matrix and polydopamine (PDA) with notable photothermal conversion capability. Starch hydrolysis, catalyzed by using α‐amylase, was accelerated in the presence of the microheater under illumination with near‐infrared light or natural sunlight at room temperature. Additionally, the methodology was extended to the preparation of microwave‐absorbing materials with the deposition of polyaniline on porous PLA matrix. The porous morphology improves the energy‐conversion efficiency. Abstract : Hot stuff ! A microheater composed of a porous polylactic acid matrix and polydopamine with notable photothermal conversion capability was designed and applied to accelerate enzymatic catalysis under NIR or natural‐sunlight irradiation (see figure), which is very promising for the cost‐effective remote manipulation of enzymatic applications.